2016 IEEE Nanotechnology Materials and Devices Conference (NMDC) 2016
DOI: 10.1109/nmdc.2016.7777086
|View full text |Cite
|
Sign up to set email alerts
|

Stability of switchable SmS for piezoresistive applications

Abstract: In this work samarium sulfide thin films have been deposited by using e-beam evaporation under H2Satmosphere. Optical and structural properties were studied in several environments. The stability in several environments allows further processing into piezoelectronic devices."(c) 2016 IEEE. Personal use of this material is permitted. Permission from IEEE must be obtained for all other users, including reprinting/ republishing this material for advertising or promotional purposes, creating new collective works f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Samarium monosulfide (SmS) is a chalcogenide material which presents a pressure-induced transition from the semiconducting (also called “blue or black state”) to the metallic (or golden) state [1,2,3,4]. At room temperature, this transition takes place at a pressure of 0.65 GPa for bulk crystals [5] and is accompanied by strong changes in the optical and electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Samarium monosulfide (SmS) is a chalcogenide material which presents a pressure-induced transition from the semiconducting (also called “blue or black state”) to the metallic (or golden) state [1,2,3,4]. At room temperature, this transition takes place at a pressure of 0.65 GPa for bulk crystals [5] and is accompanied by strong changes in the optical and electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the elastic scattering at both of these wave-vectors is significantly enhanced around T MIT . We first attempted to add a quasi-elastic term to equation (3) to allow for a broadening of the elastic line, but found that the enhancement is elastic within the energy resolution of the experiment (though fluctuations at sub-meV energies cannot be ruled out). Since the enhancement of the elastic line is well displaced from the Bragg reflections at both wave-vectors, this intensity is elastic diffuse scattering.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, the average rare-earth valence shifts as a function of an external variable such as temperature or pressure. This shift can be continuous or 1 st order, as in the case of samarium chalcogenides [3,4] for example. More recently, such phenomena have been observed in the double perovskites Ba 2 PrRu 0.9 Ir 0.1 O 6 [5,6] as well as certain cobaltite perovskites, (ACoO 3 ), that contain praseodymium cations on the A-site.…”
Section: Introductionmentioning
confidence: 99%
“…The samarium chalcogenides have shown pressure-induced transition from the semiconducting to the metallic state [14][15][16][17]. It is also called the black-golden transition; this appears at about 6.5 kbar at room temperature [14,[16][17][18][19][20].…”
Section: Iitheoretical Calculationmentioning
confidence: 99%